Pelatihan Manajemen Keselamatan Kerja Dan Penatalaksanaan Pertolongan Pertama Pada Kecelakaan Serta Antisipasi Cedera Bagi Pelatih Cabang Olahraga Soft Tennis - Kamal Firdaus; Emral Emral (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2019)
The problem of Coaching Clinic for Field Tennis Branch Trainers in West Sumatra Province was encountered in an ineffective training process, limited trainer ability in the training process, lack of skills and understanding, and minimal facilities and infrastructure. In a sense, the trainer does not have preparation in training, so that the training process is carried out less according to the actual situation. Certainly, this makes it difficult to achieve an athlete's achievement. For this reason, a solution is needed through the Coaching Clinic Activities for Field Branch Sports Field Trainers in West Sumatra Province. Problems encountered in the field: The trainer has not been able to understand and be able to apply the concept of training periodization, for this reason, it is necessary to conduct a coaching pattern about the formation of the exercise periodization concept, the trainer has not been able and skilled to develop elements of the physical condition of the Tennis Field athletes. Lack of understanding and knowledge of trainers about management and the training methodology of Field Tennis, so it needs to be equipped with the establishment of the fundamentals of management training following the sport that will be developed. Lack of values ​​and attitudes towards the development of Tennis Field sports so far, it is necessary to give tips in management in the form of entrepreneurial activities and other patterns that are not binding. In this activity, the strategic target audience was the trainers of the Tennis Field Sports Branch in West Sumatra Province, as many as 25 people were recruited in collaboration with the Executive Board of West Sumatra Province. The Coaching Clinic for Trainers in the Field of Sports in the Field in West Sumatra Province was held for 6 months, which took place at the PT.TELKOM West Sumatra Tennis Court. Method of Activity carried out by the Submission of material and demonstrations.